Photostimulation of Phox2b medullary neurons activates cardiorespiratory function in conscious rats - Kanbar, Roy (2010)
Rationale: Hypoventilation is typically treated with positive pressure ventilation or, in extreme cases, by phrenic nerve stimulation. This preclinical study explores whether direct stimulation of central chemoreceptors could be used as an alternative method to stimulate breathing. Objectives: To determine whether activation of the retrotrapezoid nucleus (RTN), which is located in the rostral ventrolateral medulla (RVLM), stimulates breathing with appropriate selectivity. Methods: A lentivirus was used to induce expression of the photoactivatable cationic channel channelrhodopsin-2 (ChR2) by RVLM Phox2b-containing neurons, a population that consists of central chemoreceptors (the ccRTN neurons) and blood pressure (BP)-regulating neurons (the C1 cells). The transfected neurons were activated with pulses of laser light. Respiratory effects were measured by plethysmography or diaphragmatic EMG recording and cardiovascular effects by monitoring BP, renal sympathetic nerve discharge, and the baroreflex. Measurements and Main Results: The RVLM contained 600 to 900 ChR2-transfected neurons (63% C1, 37% ccRTN). RVLM photostimulation significantly increased breathing rate (+42%), tidal volume (21%), minute volume (68%), and peak expiratory flow (48%). Photostimulation increased diaphragm EMG amplitude (19%) and frequency (21%). Photostimulation increased BP (4 mmHg) and renal sympathetic nerve discharge (43%) while decreasing heart rate (15 bpm). Conclusions: Photostimulation of ChR2-transfected RVLM Phox2b neurons produces a vigorous stimulation of breathing accompanied by a small sympathetically mediated increase in BP. These results demonstrate that breathing can be relatively selectively activated in resting unanesthetized mammals via optogenetic manipulation of RVLM neurons presumed to be central chemoreceptors. This methodology could perhaps be used in the future to enhance respiration in humans.